2019
DOI: 10.4103/atm.atm_258_18
|View full text |Cite
|
Sign up to set email alerts
|

Fatal and near-fatal thunderstorm asthma epidemic in a desert country

Abstract: BACKGROUND: Reports of thunderstorm asthma in the Middle East are few. This study is the first to report on cases of near-fatal and fatal thunderstorm asthma in Kuwait on December 1, 2016. METHODS: We conducted a chart review and interview with adult patients admitted to Mubarak Al-Kabir Hospital with near-fatal asthma, defined as an exacerbation requiring intubation and mechanical ventilation or hypercapnia with a PaCO 2 ≥6 kPa. Information, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although most acute asthma attacks develop over a period of days, patients with brittle asthma may present with a much more dramatic deterioration. [ 223 224 ] It is important to realize that most patients who die from an acute asthma attack had chronically uncontrolled asthma, had received suboptimal treatment with ICS, and had inadequate monitoring of their asthma. [ 225 ] Management of acute asthma is the extreme spectrum of uncontrolled asthma and represents the failure to reach adequate asthma control.…”
Section: Section 7: Management Of Acute Asthma In Adults and Adolescementioning
confidence: 99%
“…Although most acute asthma attacks develop over a period of days, patients with brittle asthma may present with a much more dramatic deterioration. [ 223 224 ] It is important to realize that most patients who die from an acute asthma attack had chronically uncontrolled asthma, had received suboptimal treatment with ICS, and had inadequate monitoring of their asthma. [ 225 ] Management of acute asthma is the extreme spectrum of uncontrolled asthma and represents the failure to reach adequate asthma control.…”
Section: Section 7: Management Of Acute Asthma In Adults and Adolescementioning
confidence: 99%
“…Ali et al . [ 35 ] reported cases of near-fatal and fatal asthma caused by storms in Kuwait on December 1 st , 2016; 17 patients were admitted with near-fatal asthma, 93.8% had a previous history of asthma, with an average duration of 9 years, 33.3% reported receiving inhaled corticosteroids from their physician and 93.8% relying only on a short-acting β2-agonist to control their asthma; 68.8% reported being outdoors during the storm and eleven patients were diagnosed with fatal asthma. Foo et al [ 45 ] reported, in individuals affected by TA, evidence of continuous loss of asthma control in those with previously well-controlled asthma and persistence of symptoms suggestive of asthma in those without a history or symptoms suggestive of previous asthma, even after 36 months of initial TA.…”
Section: Who Is At Risk Of Thunderstorm Asthma?mentioning
confidence: 99%
“…Thunderstorms have been linked to asthma epidemics, especially during the pollen seasons, and there are descriptions of asthma outbreaks associated with thunderstorms, which occurred in several cities, prevalently in Europe (Birmingham and London in the UK [6] and Naples in Italy [1,2]) and Australia (Melbourne and Wagga Wagga) [3,[4][5][6][7]. There are observations that thunderstorms occurring during pollen season can induce asthma attacks sometimes severe and near fatal asthma in pollinosis patients [1,25,35].…”
mentioning
confidence: 99%
“…The main epidemics were reported from Australia in 2010 and 2016, from London in 1994, from Naples in 2004 [2][3][4], and from Kuwait in 2020 (about data on events occurred in 2016) [5].…”
Section: To the Editormentioning
confidence: 99%